“Better at home”: Mixed methods report of intricacies in pediatric febrile neutropenia management - Eleanor T. Smeallie; Sung W. Choi; Rajen Mody; Timothy C. Guetterman; Charles N. Nessle (Cancer Medicine, 2024)
Abstract Introduction Many febrile neutropenia (FN) episodes are low risk (LR) for severe outcomes and can safely receive less aggressive management and early hospital discharge. Validated risk tools are recommended by the Children's Oncology Group to identify LR FN episodes. However, the complex dynamics of early hospital discharge and burdens faced by caregivers associated with the FN episode have been inadequately described. Methods An adapted quality‐of‐life (QoL) survey instrument was administered by a convergent mixed methods design; qualitative and quantitative data from two sources, the medical record and the mixed methods survey instrument, were independently analyzed prior to linkage and integration. Code book was informed by conceptual framework; open coding was used. Mixed methods analysis used joint display of results to determine meta‐inferences. Results Twenty‐eight patient–caregiver dyads participated with a response rate of 87%. Of the 27 FN episodes, 51.8% (14/27) were LR and 40.7% (11/27) had an early hospital discharge. The LR and early hospital discharge groups had higher mean QoL scores comparatively. Meta‐inferences are reciprocal influencers and expand the complex situation; FN negatively affects the entire family, and the benefits of hospital management were outweighed by risks and worsened symptoms, so an individualized approach to management and care at home was preferred. Conclusion Early discharge of LR FN episodes positively impacts QoL, yet risk‐stratified management for FN is intricately complex. Optimal FN management should prioritize the patient's overall health; shared decision‐making is recommended and can improve care delivery. These results should be confirmed in a larger, more heterogeneous population.